PERANCANGAN SISTEM KONTROL AYUNAN BAYI OTOMATIS DAN MONITORING SENSOR MENGGUNAKAN APLIKASI ANDROID - Nursalim Nursalim; Don E.D.G Pollo; Efraim Yosep Woso Paratu (Jurnal Media Elektro, 2021)
Significant technological developments have led to various automatic equipment that can replace human labor. Automatic technology also offers efficiency and effectiveness in all areas of human life especially for household appliances. One of the household appliances that use this system is baby equipment such as baby swings. The existing baby swings are still using conventionally with the human power. This study aims to design an automatic technology for baby cradles so it can help mothers (user) to keep monitor the baby’s condition while doing other work or even from a distance. This baby swing device is designed to use a sound sensor to detect the sound of a crying baby and a gas sensor to detect when a baby is defecating with the Arduino UNO Microcontroller as the core of the baby swing controller and Android as a control and information media to the user. Based on the results of research and testing, this automatic baby swing tool is already running well, where when the baby cries, the sound sensor will detect and move the DC Motor and display a notification on the android.